Live Streaming and Materialism as Determinants of Skincare Purchase Decisions: The Mediating Role of Hedonic Motivation Among Shopee Users - Revania Kurniawati; Imronudin Imronudin (International Journal of Economics Development Research (IJEDR), 2025)
This study investigates the influence of live streaming and materialism on skincare product purchase decisions through Hedonic Motivation among Shopee users in Solo Raya. A quantitative approach was employed, collecting primary data via structured questionnaires from 150 Gen Z respondents aged 17–26, selected through convenience sampling. The research examined four variables: Live Streaming (interactive online shopping with real-time product demonstrations), Materialism (orientation toward wealth and possessions), Hedonic Motivation (intentions driven by pleasure and social norms), and Purchase Decision (five-stage decision-making process). Measurement models assessed validity and reliability using convergent and discriminant validity, composite reliability, and Cronbach’s alpha, while structural models evaluated causal relationships via R², Q², effect size f², and Normed Fit Index. The results indicate that live streaming positively and significantly influences Hedonic Motivation, which in turn mediates its effect on purchase decisions. Materialism also positively affects Hedonic Motivation, though its impact on Buying Decision, both directly and through Hedonic Motivation, is not significant. These findings suggest that optimizing interactive and engaging live streaming experiences can enhance consumer enjoyment and drive purchases. Future research should expand the geographic scope and test other product categories.